2000
DOI: 10.1038/35036213
|View full text |Cite
|
Sign up to set email alerts
|

A cortical–hippocampal system for declarative memory

Abstract: Recent neurobiological studies have begun to reveal the cognitive and neural coding mechanisms that underlie declarative memory--our ability to recollect everyday events and factual knowledge. These studies indicate that the critical circuitry involves bidirectional connections between the neocortex, the parahippocampal region and the hippocampus. Each of these areas makes a unique contribution to memory processing. Widespread high-order neocortical areas provide dedicated processors for perceptual, motor or c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

40
968
4
15

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,478 publications
(1,043 citation statements)
references
References 93 publications
40
968
4
15
Order By: Relevance
“…A, anterior; P, posterior; L, left; R, right areas through the cortico-ponto-cerebellar pathways [8]. Also, memory disorders are probably explained by the involvement of amygdalo-hippocampal complexes, which are involved in the Papez circuit [9]. This pattern has been described recently on a population level using perfusion SPECT technique and SPM12 analysis [7], but is now apparent to the naked eye using FDG PET/CT, on an individual level.…”
Section: Discussionmentioning
confidence: 95%
“…A, anterior; P, posterior; L, left; R, right areas through the cortico-ponto-cerebellar pathways [8]. Also, memory disorders are probably explained by the involvement of amygdalo-hippocampal complexes, which are involved in the Papez circuit [9]. This pattern has been described recently on a population level using perfusion SPECT technique and SPM12 analysis [7], but is now apparent to the naked eye using FDG PET/CT, on an individual level.…”
Section: Discussionmentioning
confidence: 95%
“…This result also supports our hypothesis that the function of the hippocampus is to allow repetition of an item to allow the recovery of entorhinal activity patterns that were present when the item was previously presented. Eichenbaum (2001Eichenbaum ( , 2000 hypothesized that the hippocampus could accomplish many of the functions ascribed to it by forming a "memory space." If the hippocampus could support the rapid development of a stimulus representation that captures the temporal and contextual relationships among stimuli, this representation would presumably be extremely useful in the "flexible re-expression" of memory (Eichenbaum, Otto, & Cohen, 1994;Cohen & Eichenbaum, 1993 …”
Section: Resultsmentioning
confidence: 99%
“…The close proximity of the concept of solidity to associative strength (Eichenbaum, 2000;Kim & Baxter, 2001;McClelland, et al, 1995) and probabilistic learning (Kim & Baxter, 2001;Turke-Brown, et al, 2010) points towards an involvement of the hippocampal cortex, revealed in stronger activity for more solid compared to less solid models (Eichenbaum, 2000;Kim & Baxter, 2001;McClelland, et al, 1995;Turke-Brown, et al, 2010).…”
Section: Functional Neuroanatomymentioning
confidence: 87%
“…Statistical learning results from repeated pairing of events, i.e. stimulus familiarity, that has been proposed to be critical in extending the persistence of memory (Eichenbaum, 2000). Concisely, repeated exposure leads to solidity.…”
Section: Introductionmentioning
confidence: 99%